Strategi Usaha Pembibitan Itik Talang Benih sebagai Plasma Nutfah Provinsi Bengkulu - Handayani, Eny; Romdhon, Mustofa; Santoso, Urip (BPFP Universitas Bengkulu, 2023)
This study aims to formulate an alternative strategy for breeding Itik Talang Benih as a germplasm of Bengkulu Province. Strategy formulation is carried out using SWOT analysis. Furthermore, the formulation of strategic priorities was carried out based on the analysis of the Quantitative Strategic Planning Matrix. The results showed 10 formulations of strategic priorities, namely: 1). Optimizing the Itikn Talang Benih nursery as a germplasm of Bengkulu Province, 2) Increasing production and productivity through appropriate technology, 3). Increase cooperation, study and research of Itik Talang with universities and BPTP, 4). Increased promotion through information technology, 5). Creating business opportunities for the community around the location, 6). Development of duck cultivation in the community through the formation of breeding farm groups, 7) Formulating formal regulations in the livestock sector such to ensure the quality of the seeds produced, 8) Conducting socialization and counseling for the surrounding community, 9). Conduct environmental permit studies to support livestock business and 10) Undertake environmental management efforts and environmental monitoring efforts. It can be concluded that there were ten main strategies to maintain the sustainability of the Itik Talang Benih germplasm. Key words: Itik Talang Benih, SWOT, Quantitative Strategic Planning Matrix, germplasm. ABSTRAK Penelitian ini bertujuan merumuskan strategi alternatif usaha pembibitan itik Talang Benih sebagai plasma nutfah Provinsi Bengkulu. Penyusunan strategi dilakukan dengan menggunakan analisis SWOT. Selanjutnya rumusan prioritas strategi dilakukan berdasarkan analisis Quantitative Strategic Planning Matrix. Hasil penelitian menunjukkan terdapat 10 rumusan prioritas strategi, yaitu: 1). Optimalisasi pembibitan itik Talang Benih sebagai plasma nutfah Provinsi Bengkulu, 2) Peningkatan produksi dan produktivitas melalui Teknologi Tepat Guna, 3). Meningkatkan kerjasama, pengkajian dan penelitian itik Talang Benih dengan perguruan tinggi dan BPTP, 4). Peningkatan promosi melalui teknologi informasi, 5). Menciptakan peluang usaha bagi masyarakat sekitar lokasi (pengolahan telur asin dan pengolahan limbah), 6). Pengembangan budidaya itik di masyarakat melalui pembentukan kelompok pembibitan, 7) Menyusun peraturan formal bidang peternakan untuk menjamin kualitas bibit yang dihasilkan, 8) Melakukan sosialisasi dan penyuluhan bagi masyarakat sekitar, 9). Melakukan kajian izin lingkungan untuk mendukung usaha peternakan dan 10) Melakukan upaya pengelolaan lingkungan hidup dan upaya pemantauan lingkungan hidup. Dapat disimpulkan bahwa terdapat sepuluh strategi utama untuk mempertahankan kelestarian plasma nutfah itik Talang Benih. Kata kunci: Itik Talang Benih, SWOT, Quantitative Strategic Planning Matrix, Plasma nutfah. utama untuk mempertahankan kelestarian plasma nutfah itik Talang Benih.